1999
DOI: 10.1093/ajcn/69.5.927
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise macronutrient oxidation: a factor dependent on postexercise macronutrient intake

Abstract: Voluntary postexercise compensations in energy and macronutrient intakes play a major role in the ability of exercise to alter postexercise substrate utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
5
28
0
Order By: Relevance
“…Support for our findings is found in the studies of Burton et al (6) and Dionne et al (9). Burton et al (6) compared the effects of exercise with and without energy replacement on postprandial lipid metabolism.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Support for our findings is found in the studies of Burton et al (6) and Dionne et al (9). Burton et al (6) compared the effects of exercise with and without energy replacement on postprandial lipid metabolism.…”
Section: Discussionsupporting
confidence: 88%
“…There was no difference in total fat oxidation between conditions. These data (6,9), coupled with our findings, suggest that fat oxidation after exercise will be determined by whether the calories burned during exercise are replaced (energy balance) or not (negative energy balance) and also help to reconcile why exercise training often induces a less than expected loss of fat mass (10,35,38); if energy intake increases to compensate for the energy expended in daily exercise, then daily fat oxidation will not increase, and fat balance will be maintained.…”
Section: Discussionsupporting
confidence: 54%
“…Dionne et al (9) reported no effect of a midafternoon 60-min moderateintensity exercise bout (50% V O2max) on 24-h energy expenditure in young adult males compared with a rest day under energy balance conditions. The authors attributed the absence of postexercise changes in energy expenditure to the ingestion of a snack immediately after the 60-min exercise bout (9).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 We have also demonstrated that when carbohydrate depletion during a moderate-intensity exercise session is totally compensated in the post-exercise period, differences in post-exercise substrate oxidation are abolished. 42 Since HIES promotes a greater carbohydrate utilization, one might thus realistically infer that the increased fat oxidation observed after HIES is simply the consequence of a greater impact of this type of exercise on glycogen stores.…”
Section: Discussionmentioning
confidence: 99%